Determinants Of Customer Engagement (Ce) In Islamic Banks: Faktor-Faktor Penentu Keterlibatan Pelanggan (CE) di Bank Syariah - Alimatul Farida; Andriani Samsuri; Anshori (Journal of Islamic Economics, 2024)
Islamic banking as an institution engaged in service, must be able to cover customer needs and maintain customer relationship patterns because it is necessary to compete with conventional banks. The purpose of this article study is to determine the determinants of Customer Engagement in Islamic banks and to determine the relevance of Customer Engagement to customer loyalty in Islamic banks. The research method used in this article study uses the Systematic Literature Review (SLR) method, namely collecting previous research articles as secondary data by searching for literature collections from database sites www.scholar.google.com, https://www.scopus.com, and https://openknowledgemaps.org/ using the keywords customer engagement and customer engagement with Islamic banking. The articles collected are articles published in 2017 - 2022. The results of this article study state that the determining factors of Customer Engagement (CE) in Islamic banks are customer satisfaction, customer commitment, religious factors, Customer Relationship, partnership and brotherhood in Islam between customers and Islamic banks to achieve goals, service quality and excellence. And Customer Engagement (CE) is relevant in mediating the loyalty of Islamic bank customers.